Multisystem inflammatory syndrome in children (MIS‐C) and the prothrombotic state: Coagulation profiles and rotational thromboelastometry in a MIS‐C cohort. (4th June 2021) - Al‐Ghafry, Maha; Vagrecha, Anshul; Malik, Marium; Levine, Chana; Uster, Eliza; Aygun, Banu; Appiah‐Kubi, Abena; Vlachos, Adrianna; Capone, Christine A.; Rajan, Sujatha; Palumbo, Nancy; Misra, Nilanjana; et al.
Abstract: Background: Adults infected with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) have had high rates of thrombosis. A novel condition in children infected with SARS‐CoV‐2, multisystem inflammatory syndrome in children (MIS‐C), has limited data on their prothrombotic state or need for thromboprophylaxis. Objectives: We aimed to analyze the prothrombotic state using coagulation profiles, rotational thromboelastometry (ROTEM) parameters and clinical outcomes, to determine if this could aid in risk stratification for thromboprophylaxis. Methods: This analysis included patients (<21 years of age) with a diagnosis of MIS‐C ( n = 40) and controls (presenting with suspicion of MIS‐C but later ruled out; n = 26). Results: MIS‐C patients had higher levels of inflammatory markers including D‐dimer ( p < .0001), compared with controls, along with evidence of hypercoagulability on ROTEM with elevated evaluation of fibrinogen activity (FIBTEM) maximum clot firmness (MCF) ( p < .05). For MIS‐C patients with D‐dimers >1000 ng/ml, there was a significant correlation of FIBTEM MCF ( p < .0001) with a mean value of 37.4 (standard deviation 5.1). D‐dimer >2144 ng/ml was predictive of intensive care unit admission (area under the curve [AUC] 0.80; 95% confidence interval, 0.60–0.99; p < .01; sensitivity: 82%, specificity: 75%), and elevated FIBTEM MCF (AUC 1 for >2500 ng/ml). MIS‐C patients (50%) received enoxaparin thromboprophylaxis (in addition to aspirin) with significant improvement in their inflammatory and ROTEM parameters upon outpatient follow‐up; none developed symptomatic thrombosis. Conclusions: Despite an observed prothrombotic state, none of the MIS‐C patients (on aspirin alone or in combination with enoxaparin) developed symptomatic thrombosis. ROTEM, in addition to coagulation profiles, may be helpful to tailor thromboprophylaxis in critically ill MIS‐C patients.